2018
DOI: 10.3389/fneur.2018.00964
|View full text |Cite
|
Sign up to set email alerts
|

Early Microglial Activation Following Closed-Head Concussive Injury Is Dominated by Pro-Inflammatory M-1 Type

Abstract: Microglial activation is a pathological hallmark of traumatic brain injury (TBI). Following brain injury, activated microglia/macrophages adopt different phenotypes, generally categorized as M-1, or classically activated, and M-2, or alternatively activated. While the M-1, or pro-inflammatory phenotype is detrimental to recovery, M-2, or the anti-inflammatory phenotype, aids in brain repair. Recent findings also suggest the existence of mixed phenotype following brain injury, where activated microglia simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 62 publications
8
45
1
Order By: Relevance
“…Iba1 is a pan-microglial marker whose expression increases with microglial activation ( Hopperton et al, 2018 ). TBI induced a change in microglial phenotype to an activated M1-like state ( Figure 9 ) in line with the literature ( Madathil et al, 2018 ), as well as an elevation in pro-inflammatory mRNA and protein expression (TNF-α, IL-1β, IL-6, Figure 10 ). These changes were largely mitigated by both DP and Pom, with the former consistently demonstrating greater potency.…”
Section: Discussionsupporting
confidence: 89%
“…Iba1 is a pan-microglial marker whose expression increases with microglial activation ( Hopperton et al, 2018 ). TBI induced a change in microglial phenotype to an activated M1-like state ( Figure 9 ) in line with the literature ( Madathil et al, 2018 ), as well as an elevation in pro-inflammatory mRNA and protein expression (TNF-α, IL-1β, IL-6, Figure 10 ). These changes were largely mitigated by both DP and Pom, with the former consistently demonstrating greater potency.…”
Section: Discussionsupporting
confidence: 89%
“…A persistent activation of microglia is the hallmark of a chronic neuroinflamation. Microglial activation and its M1 polarization state is characteristically exhibited in traumatic brain injury; however, the extent to which M1 vs. M2 polarization states relate to radiation-induced changes in microglia remains unclear (8,32,102,103). Upon inflammatory trigger, microglial activation matures with sequential changes in its morphology, from resting ramified state to hyper-ramified, bushy and highly phagocytic ameboid state (101,104,105).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A has diverse biological functions including regulation of angiogenesis (i.e., the formation of new blood vessels), and elevated serum VEGF-A levels are indicative of endothelial stress and injury (17). Although some studies have reported increased VEGF-A levels in the blood following TBI, including mTBI (14,15,(18)(19)(20), to the best of our knowledge, no studies have investigated the potential associations with collision sport participation or HoC. We found that VEGF-A concentration was increased in male, but not female, footballers when compared to their relative control athletes, but that this increase did not appear to be related to HoC.…”
Section: Discussionmentioning
confidence: 99%